Service delivery during the COVID-19 pandemic: experience from the Oxford Bone Tumour and Soft Tissue Sarcoma service - Rajasekaran, RB; Whitwell, D; Cosker, TDA; Gibbons, CLMH (Elsevier, 2020)
The COVID-19 (Coronavirus disease 2019) pandemic has caused an unprecedented strain on healthcare systems across the globe. Apart from being a major hurdle to delivery of basic healthcare services, this may be associated with potential harm for cancer patients. Usually being immunocompromised, cancer patients are at a higher risk of contracting the disease and with hospitals being a potential source of the infection, an urgent need to reorganise the structure of delivery of cancer care is essential. Cancer departments must balance patient care whilst also minimising transmission among patients and healthcare professionals. The Oxford Sarcoma Service was re-structured based on the guidelines issued by the National Health Service (NHS) and the British Orthopaedic Oncology Society (BOOS) to deliver unhindered care to patients. Prioritising patients who needed urgent surgery, weighing the risk-benefit ratio while delivering adjuvant treatments and conducting regular virtual multi-disciplinary team (MDT) meetings combined with personal protection equipment (PPE) usage by all involved healthcare workers were salient features in terms of ensuring the delivery of effective care during the COVID-19 pandemic. Our new model of modus operandi during this global crisis was effective in delivering high standard of care to patients and might serve as a guide to similar units managing bone and soft tissue tumours.